Monatomic catalyst as well as preparation method and application thereof
By using porous carbon support and cascade anchoring pyrolysis method in the preparation of single atom catalysts, problems such as high cost and easy agglomeration in the preparation of existing single atom catalysts are solved, and efficient and green single atom catalyst preparation is achieved. It is suitable for monool dehydrogenation reactions and has good selectivity and economicality.
Patent Information
- Application Number
- CN202411781756.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
AI Technical Summary
The preparation of existing single-atom catalysts has problems such as high complex prices, easy agglomeration, low metal loading, and uneven overall activity, which limits its application in ethanol conversion.
Porous carbon is used as a support and a single atom catalyst is prepared by cascade anchoring method. The active metal is dispersed on the carbon support in the form of a single atom, combined with the chelating of the metal salt and the chelating agent, and then pyrolyzed again after being introduced into the nitrogen source to form an efficient single atom catalyst.
It has achieved efficient preparation of single-atom catalysts, which have the advantages of high economicality of reaction atoms, green process, energy saving and efficiency, and is suitable for monohydrogenation reactions, with high product selectivity, and by-product hydrogen can be used for hydrogenation reactions.
Smart Images

Figure CN119588430A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalyst technology, and more specifically, to a single atom catalyst and a preparation method and application thereof. Background Art
[0002] Small molecule alcohols include primary alcohols such as ethanol and n-propanol and secondary alcohols such as isopropanol. They are an important class of platform compounds with advantages such as abundant production and wide sources (Reference 1: Mika, LT; Cséfalvay, E.; Németh, Catalytic Conversion of Carbohydrates to Initial Platform Chemicals: Chemistry and Sustainability. Chem. Rev. 2018, 118 (2), 505-613.). In contrast, some aldehyde compounds and ketone compounds are difficult to prepare by conventional methods, and there are disadvantages such as pollution during the synthesis process, equipment corrosion, and high carbon emissions. Therefore, it is urgent to develop a new synthesis process to achieve the green preparation of aldehyde compounds and ketone compounds.
[0003] Take the catalytic conversion of ethanol to produce acetaldehyde as an example. At present, acetaldehyde is mainly produced by ethanol oxidation and dehydrogenation. This process reacts at 500-600°C, uses air as an oxidant, and the product after the reaction is absorbed by water, and then separated by a tower to obtain pure acetaldehyde. Due to the high reaction temperature, this process consumes a lot of energy. In particular, it needs to go through a water absorption step, which invisibly increases the separation cost. At the same time, the hydrogen and oxygen in this process react to produce water, and green hydrogen cannot be obtained (Document 2: Li Mengyue, Research on Copper-based Catalysts for Ethanol Dehydrogenation to Acetaldehyde). Finally, the silver catalyst needs to be regenerated regularly. In comparison, direct dehydrogenation of ethanol to produce acetaldehyde and hydrogen has the advantages of low reaction temperature, few by-products, and by-product green hydrogen. It is an ideal way to prepare acetaldehyde. At the same time, direct dehydrogenation of ethanol is a key step in the catalytic conversion of ethanol, and plays a role as a bridge and link in the conversion of ethanol to produce high-value chemicals. Therefore, the research on direct dehydrogenation of ethanol has important application value and theoretical significance (Reference 3: Pang, J.; Yin, M.; Wu, P.; Li, X.; Li, H.; Zheng, M.; Zhang, T., Advances in catalytic dehydrogenation of ethanol to acetaldehyde. Green Chem. 2021, 23(20), 7902-7916.).
[0004] The direct dehydrogenation of ethanol is a reversible reaction. However, existing copper-based catalysts have problems such as poor catalyst stability and easy aggregation and growth of copper particles, which adds challenges to the large-scale application of this technology (Reference 4: Li, M.; Lu, W.; He, L.; Schueth, F.; Lu, A., Tailoring the surface structure of silicon carbide support for copper catalyzed ethanol dehydrogenation. ChemCatChem 2019, 11 (1), 481-487.).
[0005] Single-atom catalysts have better catalytic activity or selectivity than traditional catalysts due to their high atom utilization, low coordination environment and controllable metal-support interaction. In the ethanol dehydrogenation reaction, single atoms are mainly divided into two categories: monodispersed single atom catalysts (Reference 5: WANG C, GARBARINO G, ALLARD LF, et al. Low-temperature dehydrogenation of ethanol on atomically dispersed gold supported on ZnZrOx. ACS Catalysis, 2016, 6(1): 210–218.; Reference 6: Yang J, Zheng J, Dun C, et al. Unveiling Highly Sensitive Active Site in Atomically Dispersed Gold Catalysts for Enhanced Ethanol Dehydrogenation. Angewandte Chemie International Edition, 2024: e202408894.; Reference 7: Ouyang M, Cao S, Yang S, et al. Atomically dispersed Pd supported on zinc oxide for selective nonoxidativeethanol dehydrogenation. Industrial & Engineering Chemistry Research, 2020, 59(6): 2648-2656.) and single-atom alloy catalysis (Reference 8: SHAN J, LIU J, LI M, et al. NiCu single atom alloys catalyze the CH bond activation in the selective non-oxidativeethanol dehydrogenation reaction. Applied Catalysis B: Environmental, 2018, 226: 534–543.; Reference 9: GIANNAKAKIS G, KRESS P, DUANMU K, et al. Mechanistic and electronic insights into a working niau single-atom alloy ethanoldehydrogenation catalyst.Journal of the American Chemical Society, 2021, 143(51): 21567–21579.). These single-atom catalysts can improve the ability of the catalyst to break the α-CH and OH bonds in ethanol, reduce the reaction activation energy, and significantly improve the reaction activity, which has important theoretical value and practical significance. .
[0006] However, the current preparation of single-atom catalysts still has disadvantages such as high complex price, easy agglomeration, low metal loading, and low overall activity, which seriously limit the application of single-atom catalysts in ethanol conversion. Summary of the invention
[0007] The purpose of the present invention is to overcome the above-mentioned defects of the prior art and to provide a single-atom catalyst and a preparation method and application thereof. The single-atom catalyst of the present invention has the advantages of a simple preparation method and cheap ligands, can directly dehydrogenate alcohol compounds to aldehydes or ketone compounds, and produce hydrogen as a by-product, has the advantages of high reaction atom economy, green process, energy saving and efficiency improvement, and has broad application prospects.
[0008] To achieve the above object, the technical solution of the present invention is as follows:
[0009] A single-atom catalyst comprises a carbon carrier and an active metal chelated on the carbon carrier; the active metal comprises one or two of nickel, copper, cobalt, iron, gold, silver, palladium and platinum; the active metal is dispersed on the carbon carrier in the form of single atoms; the loading amount of the active component in the single-atom catalyst is 0.1wt% to 6wt%.
[0010] Optionally, the specific surface area of the single atom catalyst is 500m 2 / g~2000m 2 / g.
[0011] Optionally, the active metal is a combination containing at least copper and one of nickel, cobalt, iron, gold, silver, palladium and platinum.
[0012] The present invention also discloses a method for preparing the single-atom catalyst as described above, wherein the single-atom catalyst is prepared by a cascade anchoring method through a pyrolysis method, comprising the following steps:
[0013] (1) pyrolyzing a carbon precursor under an argon atmosphere to obtain a pyrolyzed carbon precursor;
[0014] (2) acid-washing the pyrolyzed carbon precursor, followed by filtering, washing, and drying to obtain a porous carbon support;
[0015] (3) grinding the porous carbon support and activating it, followed by filtering, washing and drying to obtain an activated porous carbon support;
[0016] (4) grinding the activated porous carbon support, adding a solution containing a metal salt and a chelating agent to mix, and then filtering, washing, and drying to obtain a metal-loaded porous carbon support;
[0017] (5) The metal-loaded porous carbon carrier is ground, a nitrogen source is introduced, and then ground again and pyrolyzed to obtain the single-atom catalyst.
[0018] Optionally, in step (1), the carbon precursor includes at least one of sodium citrate, potassium citrate, magnesium citrate, ammonium citrate, and citric acid; the pyrolysis temperature is 700°C to 1000°C; the pyrolysis time is 0.5h to 24h; and the pyrolysis atmosphere includes at least one of argon, helium, and nitrogen.
[0019] Optionally, in step (2), the acid used for pickling includes at least one of hydrochloric acid, sulfuric acid, nitric acid, acetic acid, and oxalic acid; the acid concentration used for pickling is 0.5 mol / L to 10 mol / L; the pickling temperature is 20°C to 60°C; the pickling time is 6h to 24h; the drying temperature is 60°C to 120°C; the drying time is 8h to 24h; the drying method includes one of normal pressure drying, vacuum drying, and freeze drying.
[0020] Optionally, in step (3), the acid used for activation includes at least one of hydrochloric acid, sulfuric acid, nitric acid, acetic acid, and oxalic acid; the concentration of the acid used for activation is 0.5 mol / L to 10 mol / L; the activation temperature is 20°C to 140°C; the activation time is 6h to 12h; the pH of the final filtrate after washing is 7; the drying temperature is 60°C to 120°C; the drying time is 8h to 24h; the drying method includes one of normal pressure drying, vacuum drying, and freeze drying.
[0021] Optionally, step (4) specifically includes: mixing the metal salt and the chelating agent at 20°C to 60°C for 1h to 24h to obtain a solution containing the metal salt and the chelating agent, grinding the activated porous carbon carrier, adding the solution containing the metal salt and the chelating agent to mix at 20°C to 60°C for 5h to 12h, filtering, washing, and drying at 60°C to 120°C for 8h to 24h to obtain a porous carbon carrier loaded with metal.
[0022] Optionally, the metal salt includes at least one of metal nitrate, metal chloride, metal sulfate, metal phosphate and metal acetate.
[0023] Optionally, the chelating agent includes at least one of α-D-glucose, ethylenediaminetetraacetic acid, nitrilotriacetic acid, and n-ethyldiaminetetraacetic acid.
[0024] Optionally, the concentration of metal salt ions in the solution containing metal salt and chelating agent is 0.005 mol / L to 0.5 mol / L, the concentration of chelating agent is 0.2 mol / L to 10 mol / L, and the molar ratio of chelating agent to metal salt is 1 / 20 to 1 / 10.
[0025] Optionally, the drying method includes one of normal pressure drying, vacuum drying and freeze drying.
[0026] Optionally, in step (5), the nitrogen source includes at least one of melamine, o-phenanthroline, urea, nitrogen trichloride, dicyandiamide, pyridine, etc.; the mass ratio of the nitrogen source to the porous carbon in the metal-loaded porous carbon carrier is (100-1):1; the pyrolysis temperature is 700°C-1000°C; the pyrolysis atmosphere includes at least one of argon, helium and nitrogen; and the pyrolysis time is 0.5h-24h.
[0027] The present invention also discloses an application of the single-atom catalyst as described above, or the single-atom catalyst prepared by the preparation method as described above in the dehydrogenation reaction of monohydric alcohol, wherein the monohydric alcohol comprises at least one of methanol, ethanol, n-propanol, n-butanol, n-pentanol, n-hexanol, n-heptanol, n-octanol, isopropanol, isobutanol, isopentanol, isohexanol, isoheptanol, benzyl alcohol and phenylethyl alcohol; the reaction is carried out in a fixed bed reactor, the reaction pressure is 0.01MPa-0.5MPa, the reaction temperature is 150°C-400°C; the mass space velocity of the catalytic reaction is 0.1h -1 ~20h -1 .
[0028] Optionally, the reaction products are mainly aldehydes and ketone compounds; when the raw material is a monohydric primary alcohol, the product is the corresponding aldehyde; when the raw material is a secondary alcohol, the product is a ketone compound.
[0029] Optionally, the reaction product contains hydrogen; when reacting in the absence of a carrier gas, the purity of the hydrogen exceeds 99% and can be used for hydrogenation reactions; the selectivity of aldehyde and ketone compounds exceeds 95%, and the catalyst operates stably for more than 500 hours.
[0030] Implementing the embodiments of the present invention will have the following beneficial effects:
[0031] 1. The single-atom catalyst provided by the present invention uses porous carbon as a carrier, and the active metal is dispersed on the carbon carrier in the form of a single atom. Compared with the traditional impregnation method, the present invention adopts a cascade anchoring strategy through a pyrolysis method. The porous carbon is introduced into the metal salt and the chelating agent, and the nitrogen source is introduced. After pyrolysis, the active metal is dispersed on the carbon carrier in the form of a single atom. The synthesized catalyst is used in the dehydrogenation reaction of monohydric alcohol to obtain monoaldehyde and hydrogen.
[0032] 2. The present invention provides a method for preparing a single-atom catalyst, which has the advantages of simple process, less production of three wastes, low price of chelating agent, high utilization rate of metal atoms, and atomic-level dispersion of effective metals. The catalyst metal sites anchored by the nitrogen source are stable after chelation by the chelating agent.
[0033] 3. The present invention uses monohydric alcohol as raw material, which has abundant reserves, multiple varieties, sufficient sources, large output and low pollution; aldehydes and ketones produced after dehydrogenation of monohydric alcohol have wide applications in the fields of fuels, chemicals, etc. In addition, hydrogen produced as a by-product in the gas phase can be used in some hydrogenation reactions.
[0034] 4. The single-atom catalyst prepared by the present invention exhibits unique selectivity in the conversion of monohydric alcohols, produces few by-products, and significantly reduces separation costs.
[0035] 5. The single-atom catalyst provided by the present invention has good stability. When used for ethanol dehydrogenation reaction, the product is easy to separate and use. The whole process has good economy and practicality, meets the requirements of sustainable development, and has important economic value and industrial prospects in biomass conversion. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a spherical aberration electron microscope photograph of the Cu-NC catalyst of Example 1 of the present invention (the white circle represents a single Cu atom). DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.
[0038] Example 1: Preparation of Cu-NC catalyst
[0039] The preparation method of the Cu-NC catalyst of this embodiment includes: placing 20g of potassium citrate as a carbon precursor in a tube furnace and pyrolyzing it at 800°C in an argon atmosphere for 1h, the heating and cooling rate is: 5°C / min, and the argon flow rate is: 20mL / min. The pyrolyzed carbon material is dissolved in 500mL of ultrapure water, magnetically stirred at 300rpm, and filtered and washed. Then it is dissolved in 300mL of ultrapure water, magnetically stirred at 300rpm, and 2M nitric acid is added until no bubbles are generated, and it is left to stand at room temperature overnight. It is filtered and washed to pH=7 and dried in an oven at 80°C for 12h. After grinding the dried carrier, it is activated by adding 1M nitric acid, magnetically stirred at 300rpm, and left to stand overnight. It is filtered and washed to pH=7 and dried in an oven at 80°C for 12h.
[0040] Dissolve 0.0966g Cu(NO3)2·2H2O in 20mL deionized water, stir magnetically at 300rpm, and add 1.4413g α-D-glucose. After stirring for 1h, add 0.2g activated porous carbon material, stir magnetically at 300rpm for 5.5h. Filter and wash it, and dry it in an oven at 80℃ for 12h. After drying, grind it, add 1g melamine, grind it thoroughly, place it in a corundum boat, and pyrolyze it at 800℃ in an argon atmosphere in a corundum tube furnace for 1h. The heating and cooling rate is: 5℃ / min, and the argon flow rate is: 20mL / min.
[0041] Example 2: Preparation of Ni-NC catalyst
[0042] The only difference between this embodiment and embodiment 1 is that the active metal is Ni, the corresponding metal salt is nickel nitrate, and the molar ratio of the chelating agent to the metal salt is 1:20.
[0043] Example 3: Preparation of Ag-NC catalyst
[0044] The only difference between this embodiment and embodiment 1 is that the active metal is Ag, the corresponding metal salt is silver nitrate, and the molar ratio of the chelating agent to the metal salt is 1:10.
[0045] Example 4: Preparation of Fe-NC catalyst
[0046] The only difference between this embodiment and embodiment 1 is that the active metal is Fe, the corresponding metal salt is ferric nitrate, and the molar ratio of the chelating agent to the metal salt is 1:40.
[0047] Example 5: Preparation of Co-NC catalyst
[0048] The only difference between this embodiment and embodiment 1 is that the active metal is Co, the corresponding metal salt is cobalt nitrate, and the molar ratio of the chelating agent to the metal salt is 1:20.
[0049] Example 6: Preparation of Au-NC Catalyst
[0050] The only difference between this embodiment and embodiment 1 is that the active metal is Au, the corresponding metal salt is chloroauric acid, and the molar ratio of the chelating agent to the metal salt is 1:20.
[0051] Example 7: Preparation of Cu-NC-EDTA catalyst
[0052] The only difference between this embodiment and embodiment 1 is that the chelating agent is ethylenediaminetetraacetic acid (EDTA), and the molar ratio of the chelating agent to the metal salt is 1:20.
[0053] Example 8: Preparation of Cu-NC-Phen Catalyst
[0054] The difference between this embodiment and embodiment 1 is that the nitrogen source is replaced by o-phenanthroline, and the molar ratio of the chelating agent to the metal salt is 1:20.
[0055] Example 9: Preparation of NiCu-NC catalyst
[0056] The only difference between this embodiment and embodiment 1 is that the active metals are Ni and Cu, the corresponding metals are nickel nitrate and copper nitrate, and the molar ratio of the chelating agent, nickel nitrate and copper nitrate is 1:10:10.
[0057] Example 10: Preparation of PdCu-NC Catalyst
[0058] The only difference between this embodiment and embodiment 1 is that the active metals are Pd and Cu, the corresponding metals are palladium nitrate and copper nitrate, and the molar ratio of the chelating agent, palladium nitrate and copper nitrate is 1:10:10.
[0059] Example 11: Preparation of PtCu-NC Catalyst
[0060] The present embodiment is different from the embodiment 1 only in that the active metals are Pt and Cu, the corresponding metals are chloroplatinic acid and copper nitrate, and the molar ratio of the chelating agent, palladium nitrate and copper nitrate is 1:10:10.
[0061] Comparative Example 1: Preparation of Cu / C Catalyst
[0062] Compared with Example 1, the difference between this comparative example and Example 1 is that the Cu / C catalyst is impregnated. The details are as follows:
[0063] Dissolve 0.0966g Cu(NO3)2·2H2O in 1mL deionized water, add 0.2g of the unactivated carbon material in Example 1, stir vigorously under ultrasound at room temperature for 10min, let stand at room temperature overnight, then heat to 80℃ at 0.05℃ / min, and dry in an oven for 12h. After grinding, the metal-loaded carbon material is reduced at 250℃ in a tube furnace for 1h, the heating rate is 5℃ / min, the reducing gas composition is: H2:N2=5:95, and the reducing gas flow rate is 60mL / min. After cooling to room temperature, passivate with passivation gas for 8h, the passivation gas composition is: O2:N2=1:99, and the passivation gas flow rate is: 30mL / min.
[0064] Comparative Example 2: Preparation of Cu / AC Catalyst
[0065] The only difference between this comparative example and comparative example 1 is that the carrier is coconut shell carbon.
[0066] Reaction Example 1
[0067] The catalytic conversion experiment was carried out in a fixed bed reactor under the following specific conditions: the catalysts prepared in Examples 1-11 and Comparative Examples 1-2 were used to carry out the dehydrogenation reaction of monohydric alcohol, the reaction temperature was 220°C, the reaction pressure was 0.01 MPa, and the reaction mass space velocity was 1.1 h -1 The reaction time is 24h, the amount of catalyst used is 0.1g, the catalyst is added to the fixed bed reactor, and nitrogen is bubbled; or it is pumped, the raw material is gasified and passes through the catalyst bed, and the gas phase product is analyzed by online gas chromatography.
[0068] The reaction results of using the catalysts prepared in Examples 1-11 and Comparative Examples 1-2 for ethanol dehydrogenation are shown in Table 1.
[0069] Table 1 Results of ethanol catalytic dehydrogenation reaction using the catalysts of Examples 1-11 and Comparative Examples 1-2
[0070]
[0071] Table 1 compares the changes in products of ethanol dehydrogenation reactions on different catalysts. From the reaction data, it can be seen that compared with the Cu-C catalyst or Cu-AC catalyst of the comparative example, the single-atom catalyst prepared by thermal decomposition in the embodiment of the present invention has good reaction activity and product selectivity. Using the Cu-NC catalyst of Example 1, the conversion rate of ethanol reached 40.1%, the selectivity of acetaldehyde reached 98.4%, and the selectivity of hydrogen reached 99.5%, showing good and excellent product selectivity. In addition, NiCu, PdCu and PtCu catalysts also have excellent acetaldehyde and hydrogen selectivity. In comparison, the catalyst prepared by the impregnation method (Comparative Examples 1-2) is rapidly deactivated and produces a large amount of by-products.
[0072] Reaction Example 2
[0073] The specific reaction conditions are the same as those in Reaction Example 1, except that the monohydric alcohol is expanded from ethanol to other alcohols. The catalyst prepared in Example 1 is used for the catalytic dehydrogenation reaction of monohydric alcohol (reaction temperature 220°C, mass space velocity: 1.1h -1 , reaction time is 24h), and the results are shown in Table 2.
[0074] Table 2 Conversion results of different monohydric alcohols on Cu-NC catalyst
[0075]
[0076] From the reaction data in Table 2, we can see that although the type of monohydric primary alcohol has changed, it can be converted into corresponding aldehyde compounds and hydrogen (hydrogen selectivity is greater than 99%), showing good universality. In addition, when monohydric secondary alcohol is used as the raw material, the product is mainly ketone compounds, and the product selectivity is also greater than 95%.
[0077] Reaction Example 3
[0078] Except for the reaction conditions specially described in Table 3, other reaction conditions are the same as those in Reaction Example 1. The results of using the catalyst Cu-NC in Example 1 for catalytic dehydrogenation of ethanol (220° C., 24 h) are shown in Table 3.
[0079] Table 3 Results of ethanol catalytic dehydrogenation over Cu-NC catalyst under different conditions
[0080]
[0081] By changing the reaction conditions, the ethanol conversion rate can reach 78.9% and the selectivity of acetaldehyde and hydrogen can reach 99%.
[0082] Reaction Example 4
[0083] Except for the reaction conditions specially indicated in Table 4, other reaction conditions were the same as those in Reaction Example 1. The results of using the catalyst Cu-NC in Preparation Example 1 for ethanol catalytic dehydrogenation (220°C, space velocity 1.1 h -1 , 24h), as shown in Table 4.
[0084] Table 4 Ethanol catalytic results on Cu-NC catalysts prepared under different conditions
[0085]
[0086] The concentration of the copper nitrate solution in the catalyst preparation method, that is, the loading of metallic copper in the catalyst, has little effect on the selectivity of acetaldehyde, but has a greater impact on the conversion rate of ethanol. In particular, when the loading of metallic copper is low or high, the catalyst activity is significantly reduced.
[0087] Reaction Example 5
[0088] Except for the reaction conditions specially indicated in Table 5, other reaction conditions were the same as those in Reaction Example 1. The results of using the catalyst Cu-NC in Preparation Example 1 for ethanol catalytic dehydrogenation (220°C, space velocity 1.1 h -1 ), as shown in Table 5.
[0089] Table 5 Ethanol catalytic results on Cu-NC catalysts prepared under different conditions
[0090]
[0091]
[0092] The types of chelating agent and nitrogen source in the catalyst preparation method have a great influence on the conversion of the product. When the nitrogen source is ethylamine, the conversion rate of ethanol is only 11.4%, and the product selectivity is low.
[0093] Reaction Example 6
[0094] The stability test was carried out using the Cu-NC catalyst prepared in Preparation Example 1, the reaction time was 500 hours, and the reaction conditions were the same as those in Reaction Example 1. The comparison of the experimental results of the present invention with the results of the prior art is shown in Table 6.
[0095] Table 6 Comparison of ethanol dehydrogenation catalysts in the present invention and prior art
[0096]
[0097] Table 7 Comparison of space-time yield of copper-catalyzed ethanol dehydrogenation catalysts in the present invention and the prior art
[0098]
[0099]
[0100] From the results in Tables 6 and 7, it can be seen that the experimental results of the present invention have relatively outstanding substantial progress in terms of reaction activity, catalyst stability, and unit space-time yield. The catalysts of the present invention are mostly non-precious metals, the reaction conditions are milder, and it has ultra-high stability and high practicality.
[0101] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A single atom catalyst, characterized in that: The single atom catalyst comprises a carbon support and an active metal chelated on the carbon support; The active metal includes one or two of nickel, copper, cobalt, iron, gold, silver, palladium and platinum; The active metal is dispersed in the carbon support in the form of single atoms; The loading amount of the active component in the single atom catalyst is 0.1 wt% to 6 wt%.
2. The single atom catalyst according to claim 1, characterized in that The specific surface area of the single atom catalyst is 500 m 2 / g~2000m 2 / g.
3. The single atom catalyst according to claim 1, characterized in that The active metal is a combination containing at least copper and one of nickel, cobalt, iron, gold, silver, palladium and platinum.
4. A method for preparing a single atom catalyst as claimed in any one of claims 1 to 3, characterized in that: The single-atom catalyst is prepared by a cascade anchoring method through a pyrolysis method, comprising the following steps: (1) pyrolyzing a carbon precursor under an argon atmosphere to obtain a pyrolyzed carbon precursor; (2) acid-washing the pyrolyzed carbon precursor, followed by filtering, washing, and drying to obtain a porous carbon support; (3) grinding the porous carbon support and activating it, followed by filtering, washing and drying to obtain an activated porous carbon support; (4) grinding the activated porous carbon support, adding a solution containing a metal salt and a chelating agent to mix, and then filtering, washing, and drying to obtain a metal-loaded porous carbon support; (5) The metal-loaded porous carbon carrier is ground, a nitrogen source is introduced, and then ground again and pyrolyzed to obtain the single-atom catalyst.
5. The preparation method according to claim 4, characterized in that: In step (1), the carbon precursor includes at least one of sodium citrate, potassium citrate, magnesium citrate, ammonium citrate, and citric acid; The pyrolysis temperature is 700°C to 1000°C; the pyrolysis time is 0.5h to 24h; The pyrolysis atmosphere includes at least one of argon, helium and nitrogen.
6. The preparation method according to claim 4, characterized in that: In step (2), the acid used for pickling includes at least one of hydrochloric acid, sulfuric acid, nitric acid, acetic acid, and oxalic acid; The acid concentration used in the pickling is 0.5mol / L to 10mol / L; The pickling temperature is 20°C to 60°C; The pickling time is 6h to 24h; The drying temperature is 60°C to 120°C; the drying time is 8h to 24h; The drying method includes one of normal pressure drying, vacuum drying and freeze drying.
7. The preparation method according to claim 4, characterized in that: In step (3), the acid used for activation includes at least one of hydrochloric acid, sulfuric acid, nitric acid, acetic acid, and oxalic acid; The acid concentration used in the activation is 0.5 mol / L to 10 mol / L; The activation temperature is 20°C to 140°C; The activation time is 6h to 12h; The washing is performed until the pH of the final filtrate is 7; The drying temperature is 60°C to 120°C; the drying time is 8h to 24h; The drying method includes one of normal pressure drying, vacuum drying and freeze drying.
8. The preparation method according to claim 4, characterized in that: Step (4) specifically comprises: mixing a metal salt and a chelating agent at 20°C to 60°C for 1h to 24h to obtain a solution containing the metal salt and the chelating agent, grinding the activated porous carbon carrier, adding the solution containing the metal salt and the chelating agent to mix at 20°C to 60°C for 5h to 12h, filtering, washing, and drying at 60°C to 120°C for 8h to 24h to obtain a porous carbon carrier loaded with metal; The metal salt includes at least one of metal nitrate, metal chloride, metal sulfate, metal phosphate and metal acetate; The chelating agent includes at least one of α-D-glucose, ethylenediaminetetraacetic acid, nitrilotriacetic acid, and n-ethyldiaminetetraacetic acid; The concentration of the metal salt ions in the solution containing the metal salt and the chelating agent is 0.005 mol / L to 0.5 mol / L, the concentration of the chelating agent is 0.2 mol / L to 10 mol / L, and the molar ratio of the chelating agent to the metal salt is 1 / 20 to 1 / 10; The drying method includes one of normal pressure drying, vacuum drying and freeze drying.
9. The preparation method according to claim 4, characterized in that: In step (5), the nitrogen source includes at least one of melamine, o-phenanthroline, urea, nitrogen trichloride, dicyandiamide, pyridine, etc.; The mass ratio of the nitrogen source to the porous carbon in the metal-loaded porous carbon carrier is (100-1):1; The pyrolysis temperature is 700°C to 1000°C; The pyrolysis atmosphere includes at least one of argon, helium and nitrogen; The pyrolysis time is 0.5h to 24h.
10. Use of the single atom catalyst as claimed in any one of claims 1 to 3, or the single atom catalyst prepared by the preparation method as claimed in any one of claims 4 to 9 in the dehydrogenation reaction of monohydric alcohol, characterized in that: The monohydric alcohol includes at least one of methanol, ethanol, n-propanol, n-butanol, n-pentanol, n-hexanol, n-heptanol, n-octanol, isopropanol, isobutanol, isopentanol, isohexanol, isoheptanol, benzyl alcohol, and phenylethyl alcohol; The reaction is carried out in a fixed bed reactor at a reaction pressure of 0.01 MPa to 0.5 MPa and a reaction temperature of 150° C. to 400° C. The mass space velocity of the catalytic reaction is 0.1 h -1 ~20h -1 .
Citation Information
Patent Citations
Monatomic catalyst prepared based on surface immobilizing method
CN111013576A
Porous carbon-loaded monatomic metal nitrogen coordination composite material and preparation method thereof
CN111620311A
Preparation method and application of alloy monatomic catalyst
CN114054023A
Preparation method of carbon-based monatomic catalyst
CN114864967A
Preparation method and application of metal high-load type monatomic catalyst
CN115301272A